Effects of Thematic Curriculum on Learners' Acquisition of English Skills in Selected Primary Schools of Nkuringo Town Council Kisoro District-Uganda. - Niyizi, Winfred (Kabale University, 2024)
This study aimed to evaluate the effectiveness of the thematic curriculum in fostering English language skills among learners. The research has three primary objectives: first, to assess the level of English skills acquisition among students in schools implementing the thematic curriculum; second, to compare these skills with those of learners in schools utilizing traditional curriculum methods; and third, to identify the strengths and weaknesses of the thematic curriculum in promoting English language proficiency. A mixed-methods approach collected data from a diverse sample of students and educators across various educational institutions. Preliminary findings suggest that while the thematic curriculum enhances certain aspects of language acquisition, disparities exist when compared to traditional methods. This research highlights critical insights into curriculum design and pedagogical strategies, offering implications for educational policy and practice to improve English language education.